CONTRIBUTION OF THE UN REGIONAL FUND AND ROYALTIES FROM MINERAL AND ENERGY NATURAL RESOURCES TO REVENUE SHARING FUNDS : Empirical Study Across All Provinces of Kalimantan - Suwarno, Try Edi; Djajasinga, Nico Djundharto; Rabani, Siti Sarah Al (UNPERBA, 2025)
This study aims to analyze the influence of Regional Land and Building Tax (PBB) and royalties from mineral and coal natural resources (SDA Minerba) on Revenue Sharing Funds (DBH) across all provinces in Kalimantan during the 2022–2024 period. The data used are secondary data, including the realization of PBB, Minerba royalties, and DBH from local government financial reports. The study adopts a quantitative approach using panel data regression and the Fixed Effect Model, selected based on Chow and Hausman tests. The results show that Minerba royalties have a statistically significant effect on DBH, whereas Regional PBB does not show a significant influence. These findings indicate that revenue from extractive sectors plays a dominant role in shaping regional fiscal capacity in Kalimantan. The study recommends optimizing PBB collection and diversifying revenue sources to strengthen sustainable regional fiscal structures.